PHYSICOCHEMICAL CONDITIONS OF IRON-TITANIUM OXIDE FORMATION IN ROCKS OF THE KONDER ALKALIC ULTRAMAFIC PLUTON - Malich K.N.; Avdontsev S.N. (My University, 1987)
Olivinite was developed in the emplacement front of clinopyroxenite and gabbro, and its thickness is directly proportional to the combined thickness of these clinopyroxene-bearing rocks. Oxidation of dunite olivine and the resulting formation of olvinite could have occurred within a narrow fO2 range (10-2 to 10-5) upon cooling below temperatures of 550° to 530°C. The variation in fluid regime of dunite-oxidizing clinopyroxenite and gabbro upon such cooling, as reflected in the evolution of iron-titanium oxide compositions, is described by the curve derived from an equation given in the paper. Consequently, these clinopyroxene-bearing rocks would have oxidized dunite only if their temperature has been no lower than 800°C, and that of the dunite no higher than 550°C. The process that produced olivinite should be classified as one of high-temperature metasomatic alteration at the contact between two physico-chemically contrasting rock media. Overall, the data seem to support the restite model of emplacement of the Kondyor pluton, even if they are regarded as semiquantitative.